Policy implementation and outcome evaluation: establishing a framework and expanding capacity for advocacy organizations to assess the impact of their work in public policy - Laurie P. Whitsel; Sally Honeycutt; Reyna Radcliffe; Janay Johnson; Paul J. Chase; Philip Noyes (BMC, 2024)
Abstract Advocacy organizations can play a crucial role in evaluating whether legislation or regulation has had its intended effect by supporting robust public policy implementation and outcome evaluation. The American Heart Association, working with expert advisors, has developed a framework for effective evaluation that can be used by advocacy organizations, in partnership with researchers, public health agencies, funders, and policy makers to assess the health and equity impact of legislation and regulation over time. Advocacy organizations can use parts of this framework to evaluate the impact of policies relevant to their own advocacy and public policy efforts and inform policy development and guide their organizational resource allocation. Ultimately, working in partnership, advocacy organizations can help bring capacity, commitment and funding to this important implementation and outcome evaluation work that informs impactful public policy for equitable population health and well-being.